How to measure human capital for reporting purposes? - Renkas, Iryna (SPC Journal of Social Sciences, 2023)
The aim of this article is to present thermodynamic models of human capital measurement and their usefulness for the purpose of compiling information on the level of payment of human capital of a company's employees. A study of the literature on the subject reveals the role of Polish researchers in this area.